Teacher’s Understanding and Practice on Implementing Higher Oder Thinking Skills (HOTS) in EFL Classroom - Nurul Insani Rasyid; Haryanto Atmowardoyo; Qashas Rahman (Celebes Journal of Language Studies, 2021)
This study focuses on Teacher’s understanding and practice on Implementation Higher Order Thinking Skills (HOTS) in speaking classroom. The study aims to find out the result of (1) the teacher’s understanding and practice about the concept of Higher Order Thinking Skills on implementing HOTS in EFL classroom, (2) students’ response about Implementing Higher Order Thinking Skills (HOTS) in EFL classroom. The method of the research uses qualitative descriptive. The study is conducted at SMP Telkom Makassar. The subjects of this study are 32 respondents. In collecting data, the research uses Questionnaire and Observation. In technique data analysis uses three steps namely Data collection, Data reduction and data display. The result of the study shows that (1) the teacher understands and practice about the implementation of Higher Order Thinking skills is minimum. The result showed that the teacher has minimal understanding and practice about the concept of higher order thinking skills (HOTS) on implementing HOTS in EFL classroom. Teacher still confused about what is mean by the definition of HOTS. The teacher was mentioned the HOTS as learning method, not an ability that the students have to master it. (2) Based on the research that, students’ response about implementing HOTS in teaching classroom were still low. Some students tended to be more silent then showing their response or their opinion.